Draft Eighth Five-Year Plan, 1990-95 and Annual Plan, 1991-92 Maharashtra State Part-II - Planning Commission (Planning Commission, 1990)
Total estimated cost of saline land Reclamation Scheme Phase I is Rs. 18.05 crores. Out of which, expenditure incurred up to the end of VIIth Five-Year Plan (i.e. March 1990) is Rs:. 14.67 crores. So, the spill over cost as on 1st April 1990 is Rs. 3.38 crores. This balance work is to be completed in the first two years of VIIIth Five-Year Plan. So, considering 20 per cent escalation, total requirement of outlay during the VIIIth Five-Year Plan is Rs. 4.06 crore, which is completely Central assistance.
Maharashtra State